Challenge of long-term benzodiazepine use in primary care: insights from a real-world cohort study in Catalonia - Marc Saez; Alexandra Lelia Dima; Blanca Lumbreras; Ignacio Aznar-Lou; María Teresa Peñarrubia-María; Antoni Serrano-Blanco; Lucy Anne Parker; Marta Puig-García; Marina Fuente-Moreno; Elsa Lopez-Pintor; Joan Domenech Abella; Adolfo Figueiras Guzmán; et al. (Family Medicine and Community Health)
Introduction Long-term use of benzodiazepines (BZD) triggers health problems. Although Spain leads European use of BZD, the number of long-term users (LTUs) remains unknown.Objective The aim of the study is to estimate the proportion of primary care (PC) patients who initiate a BDZ prescription that subsequently become LTU and to identify its associated factors.Design Retrospective real-world data cohort.Setting and participant It included the population over 15 years with a new prescription of BZD in PC in Catalonia. Users were considered LTU if they had been dispensed at least three prescriptions within 3 months. Sociodemographic characteristics of patients and prescribers, pathologies, previous BZD use, number and type of visits, and prescription quality standard were considered. We estimated the proportion of LTU among patients with a new prescription, stratified by age and sex, and estimated risk factors by multivariate generalised linear models.Result 100 638 users with a new BZD prescription were included. 27.1% were LTU at 3 months and 14.5% at 6 months. LTU increases with age and is higher in women. Predictors of LTU are Spanish nationality, living in rural areas, having a mental illness, having used BZD, having virtual visits or not meeting pharmacy-therapeutic quality standards.Conclusion The number of patients who develop LTU is high, especially in the elderly. Exploring the causes of this phenomenon could contribute to the development of future interventions.